FROM CONVERGENCE TO DATAFICATION OF CYBER JOURNALISM IN THE AMAZON: a focus on OLiberal.com and DOL - Sousa, Maíra Evangelista de; Martins, Elaide (Brazilian journalism research, 2024)
ABSTRACT – This work aims to understand the main properties of cyber journalism on two news portals from the Brazilian Amazon: OLiberal.com and DOL. The qualitative research consisted of direct observation of the products, semi-structured interviews conducted with the executive editors of these online newspapers, and description and analysis of data. The results point to four properties that make up the narrative of this article (convergence processes, mobility, platformization, and datafication) and show that these media outlets have invested in analyzing metrics and producing news for social networking sites and search engines, following the global logic of large technology companies and resulting in changes to the structure of newsrooms, production routines, professional culture, and journalistic products in convergent scenarios. RESUMO – Este trabalho objetiva compreender as principais propriedades do ciberjornalismo em dois portais de notícias da Amazônia Brasileira: OLiberal.com e DOL. A pesquisa qualitativa foi feita por meio de observação direta dos produtos e entrevistas semiestruturadas com os editores executivos desses ciberjornais; descrição e análise dos dados. Os resultados apontam quatro propriedades, as quais conduziram a narrativa do artigo (processos de convergência, mobilidade, plataformização e dataficação) e indicam que esses veículos têm investido em análise de métricas e em produção de notícias para sites de redes sociais e buscadores, submetendo-se à logica global das grandes empresas de tecnologia e acarretando transformações na estrutura das redações, nas rotinas produtivas, na cultura profissional e nos produtos jornalísticos em cenários convergentes. RESUMEN – Este trabajo tiene como objetivo comprender las principales propiedades del ciberperiodismo en dos portales de noticias de Amazonía Brasileña: OLiberal.com y DOL. La investigación cualitativa se realizó en dos etapas: observación directa de los productos y entrevistas semiestructuradas a los editores ejecutivos de estos cibermedios; descripción y análisis de datos. Los resultados apuntan a propiedades actuales que guiaron la narrativa del artículo (procesos de convergencia, movilidad, plataformización y datificación) e indican que los medios de comunicación invierten en análisis de métricas y producción de noticias para sitios de redes sociales y buscadores, sometiéndose a la lógica global de las grandes empresas tecnológicas y propiciando transformaciones en la estructura de las redacciones, las rutinas de producción, la cultura profesional y en los productos periodísticos en escenarios convergentes.